Use of Leaflets Compliance With Slogans Drinking Drugs Assertif And Cured Motivation in Tuberkulosis Patients - Herry Prasetyo; Petrus Nugroho DS; Ulfah Agus Sukrillah (Jurnal Riset Kesehatan, 2012)
The goal of this research is to investigate the effect of using assertive leaflet towards the obedience consuming the drugs and motivation of recovering from tuberculosis. The research design is quasy experiment. Pre and post test with control group design was used in this research. The result of the research shows that there was a significant results in the intervention group group before and after using assertive leaflet towards the obedience consuming the drugs whereas p value 0,008 less than 0,05, on the other hand there was no change before and after in the control group. Moreover, in term of motivation of recovering from tuberculosis, the intervention group has p value 0,007 less than 0,05.